Tribbles 3 deficiency promotes atherosclerotic fibrous cap thickening and macrophage-mediated extracellular matrix remodelling - Martinez-Campesino, Laura; Kocsy, Klaudia; Cañedo, Jaime; Johnston, Jessica M.; Moss, Charlotte E.; Johnston, Simon A.; Hamby, Stephen; Goodall, Alison H.; Redgrave, Jessica; Francis, Sheila E.; Kiss-Toth, Endre; Wilson, Heather L. (Frontiers in Cardiovascular Medicine, 2022)
Tribbles 3 (TRIB3) modulates lipid and glucose metabolism, macrophage lipid uptake, with a gain-of-function variant associated with increased cardiovascular risk. Here we set out to examine the role of this pseudokinase in atherosclerotic plaque development. Human endarterectomy atherosclerotic tissue specimens analysed by immunofluorescence showed upregulated TRIB3 in unstable plaques and an enrichment in unstable regions of stable plaques. Atherosclerosis was induced in full body Trib3KO and Trib3WT littermate mice by injecting mPCSK9 expressing adeno-associated virus and western diet feeding for 12 weeks. Trib3KO mice showed expanded visceral adipose depot while circulatory lipid levels remained unaltered compared to wildtype mice. Trib3KO mice aortae showed a reduced plaque development and improved plaque stability, with increased fibrous cap thickness and collagen content, which as accompanied by increased macrophage content. Analysis of both mouse and human macrophages with reduced TRIB3 expression showed elongated morphology, increased actin expression and altered regulation of genes involved in extracellular matrix remodelling. In summary, TRIB3 controls plaque development and may be atherogenic in vivo. Loss of TRIB3 increases fibrous cap thickness via altered metalloproteinase expression in macrophages, thus inhibiting collagen and elastic fibre degradation, suggesting a role for TRIB3 in the formation of unstable plaques.